![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{1}{x^2-x+1}+1-\frac{x^2+2}{x^3+1}\)
+) Đkxđ: \(\hept{\begin{cases}x^2-x+1\ne0\\x^3+1\ne0\end{cases}\Leftrightarrow\hept{\begin{cases}x^2-2.x.\frac{1}{2}+\left(\frac{1}{2}\right)^2+\frac{3}{4}\ne0\\x^3\ne-1\end{cases}\Leftrightarrow}\hept{\begin{cases}\left(x-\frac{1}{2}\right)^2+\frac{3}{4}\ne0\left(lđ\right)\\x\ne-1\end{cases}}}\)
+) \(A=\frac{1}{x^2-x+1}+1-\frac{x^2+2}{x^3+1}\)
\(=\frac{1}{x^2-x+1}+1-\frac{x^2+2}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(=\frac{x+1+x^3+1-x^2+2}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(=\frac{x^3-x^2+x+4}{\left(x+1\right)\left(x^2-x+1\right)}\)
P/s: ko chắc
Huhu luoi qua
a) \(\frac{1}{x^2-x+1}+1-\frac{x^2+2}{x^3+1}\)
\(=\frac{1}{x^2-x+1}+1-\left(\frac{x^2+2}{x^3+1}\right)\)
\(=\frac{x^5-2x^4+3x^3-2x^2+x}{x^5-x^4+x^3+x^2-x+1}\)
\(=\frac{x\left(x^4-2x^3+3x^2-2x+1\right)}{\left(x+1\right)\left(x^4-2x^3+3x^2-2x+1\right)}\)
\(=\frac{x}{x+1}\)
b) \(\frac{7}{x}-\frac{x}{x+6}+\frac{36}{x^2+6x}\)
\(=\frac{-x^2+7x+78}{x^2+6x}\)
\(=\frac{\left(-x-6\right)\left(x-13\right)}{x\left(x+6\right)}\)
\(=\frac{-x+13}{x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 1 : x2-y2+2yz-z2=-(y2-2yz+z2-x2) Câu 2: x2-2xy+y2-xz+yz=(x2-2xy+y2)-xz+yz
=-(y-z)2 -x2 =(x-y)2-z(x-y)
=-(y-z-x)(y-z+x) =(x-y)(x-y-z)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x^2+2}{2xy^3}-\frac{2x+2}{2xy^3}=\frac{x^2+2-2x-2}{2xy^3}=\frac{x^2-2x}{2xy^3}=\frac{x\left(x-2\right)}{2xy^3}=\frac{x-2}{2y^3}\)
\(\frac{4}{x-5}-\frac{1}{x+5}+\frac{13x-x^2}{25-x^2}=\frac{4}{x-5}-\frac{1}{x+5}+\frac{x^2-13x}{x^2-25}\)
\(=\frac{4\left(x+5\right)}{\left(x-5\right)\left(x+5\right)}-\frac{x-5}{\left(x-5\right)\left(x+5\right)}+\frac{x^2-13x}{\left(x-5\right)\left(x+5\right)}\)
\(=\frac{4x+20-x+5+x^2-13x}{\left(x-5\right)\left(x+5\right)}\)
\(=\frac{x^2-10x+25}{\left(x-5\right)\left(x+5\right)}=\frac{\left(x-5\right)^2}{\left(x-5\right)\left(x+5\right)}=\frac{x-5}{x+5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\frac{x+1}{2x+6}+\frac{2x+3}{x^2+3x}=\frac{x+1}{2\left(x+3\right)}+\frac{3x+2}{x\left(x+3\right)}\)
\(=\frac{x^2+x}{2x\left(x+3\right)}+\frac{6x+4}{2x\left(x+3\right)}=\frac{x^2+7x+4}{2x\left(x+3\right)}\)
b, Sua de : \(\frac{3}{2x+6}-\frac{x-6}{2x^2+6x}=\frac{3}{2\left(x+3\right)}-\frac{x-6}{2x\left(x+3\right)}\)
\(=\frac{3x}{2x\left(x+3\right)}-\frac{x-6}{2x\left(x+3\right)}=\frac{2x+6}{2x\left(x+3\right)}=\frac{1}{x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2x^2-11x}{2xy}+\frac{5y-x}{y}+\frac{x+2y}{x}\)
\(=\frac{2x^2-11x+\left(5y-x\right)2x+\left(x+2y\right)2y}{2xy}\)
\(=\frac{2x^2-11x+10xy-2x^2+2xy+4y^2}{2xy}=\frac{12xy-11x+4y^2}{2xy}\)
x2+2y2-2xy+6x-6y+27
= x2-2xy+y2+y2+6x-6y+27
= (x-y)2+y2+6(x-y) + 27
= (x-y)2+6(x-y) + 9+ 18+ y2
= (x-y+3)2+ 18+ y2